The divide - Evans, Nicholas 1950- (London Bantam Press, 2005)
Two backcountry skiers find the body of a young woman embedded in the ice of a remote mountain creek. All through the night, police work with arc lights and chain saws to dig her out. But identification doesn't take as long. Abbie Cooper is wanted for murder and acts of eco-terrorism, and her picture is on law-enforcement computers all across America. But just how did she die? And what was the trail of events that led this joyous, golden child of a loving family so tragically astray?
Keywords: Ecoterrorism -- Fiction; Montana -- Fiction; Western stories; Love stories